Prehospitalno odlaganje u pacijenata sa akutnim bolom u grudima - Milovanović, Lidija D; Živanović, Slavoljub R (Scripta Medica, 2020)
Introduction: Incidence of chest pain and discomfort varies in general population between 2 % and 5 %. Total prehospital delay involves two components: the time it takes for patients to recognise their symptoms as severe and seek medical attention, ie the decision-making time, and the time from seeking help to hospital admission, ie the transport time. Scope of the study was to analyse time loss in patients with chest pain hesitating to contact healthcare services, as well as distribution of acute myocardial infarction (AMI) and angina pectoris (AP) among them. Methods: Retrospective analysis of medical records of physicians working at the emergency medical services (EMS) Department of the City of Belgrade, Serbia, from 20 April 2006 to 22 July 2013 on a total of 5,310 completed field interventions. When placing a call to the EMS, 10.43 % of patients cited chest pain as a major symptom. After deducting all those ones who denied having the symptom on examination thereafter and those for whom there were no data, 349 patients remained, ie 6.57 % of the total number of calls available for analysis. Results: The average time between the onset of chest pain and the decision to call the EMS was 11.97 h, median 2 h and mode 1 h. Patient’s minimum prehospital delay was 2 min and the maximum was 20 days. Most patients who experienced chest pain or discomfort waited less than an hour before calling the EMS. Most commonly diagnoses made for a symptom of chest pain were AMI and AP, ie AMI with 12.32 % of the total diagnoses, as well as the elevated arterial pressure. There were more female patients, with no difference found among the age groups. Conclusion: For the majority of patients with chest pain and discomfort presented in this paper the decision-making time was up to one hour, with cardiovascular causes being the at the top of the list.